Sociality and self-awareness in animals - Lei, Yanyu (Frontiers in Psychology, 2023)
Recognizing one’s mirror reflection as oneself appears to be a simple task, but beyond humans, very few animals have consistently demonstrated this capability. Mirror self-recognition is indicative of self-awareness, which is one’s capacity for self-directed knowledge. This Perspective reviews literature from the past fifty years on animal self-recognition and evaluates twenty different species. The goal was to determine a common characteristic shared by all self- aware animals that allow for this advanced cognitive capability. This paper found that only social animals have demonstrated self-awareness while no solitary species has ever shown this capability. This is supported by the social intelligence hypothesis, which posits that social animals are more cognitively sophisticated than solitary ones because their brains evolved to process the more complex social environment around them. Given the available information, this article proposes that social animals are more likely to be self-aware than solitary species.